STRATEGI PEMILIHAN LOKASI PERMUKIMAN DI KAWASAN BUNTU PUNE KABUPATEN TORAJA UTARA SULAWESI SELATAN - Rullah, Rany Martha (Humanis, 2016)
The cosmology of Toraja people who came from the trust of Aluk Todolo greatly affect the location and direction toward of each component contained in an area. Microcosms should be always in harmony with the macrocosm is a major concern in the division classification vertically or horizontally. Various ceremonies which performed must always be guided to the subdivision. Tongkonan considered as a single entity classifying indigenous microcosm as a replica of the macrocosm. Tongkonan as a symbol of the microcosms, where the ceremony was centered, persuaded to the tendency and types of ceremonies were held. Early settlement of Buntu Pune area was in Buntu Boro who makes access difficult to reach. The fort defenses protect overseers to protect settlements from enemy attack. Abundant natural resources becomes a major consideration for the founder of Buntu Boro to move to Buntu Pune. The results showed that the factor of local trust concept oriented to the wind directions effect on the layout of the eight components that are in a residential area in Buntu Pune. The eight components, namely; Tongkonan, Alang Sura’, fort defenses, Panglambaran, Kombong, Bubun, Rante, and Liang, which in every element has a relationship with each other.
Keywords: Cosmology, settlement, Tongkonan, Toraja